Polymer crowders and protein crowders act similarly on protein folding stability. Issue 5 (23rd January 2013) - Zhou, Huan-Xiang
Abstract : Recently a polymer crowder and two protein crowders were found to have opposite effects on the folding stability of chymotrypsin inhibitor 2 (CI2), suggesting that they interact differently with CI2. Here we propose that all the macromolecular crowders act similarly, with an entropic component favoring the folded state and an enthalpic component favoring the unfolded state. The net effect is destabilizing below a crossover temperature but stabilizing above it. This general trend is indeed observed in recent experiments and hints experimental temperature as a reason for the opposite crowding effects of the polymer and protein crowders. Abstract : ► A unified mechanism is proposed for macromolecular crowding on folding stability. ► Enthalpy and entropy of crowding favor unfolded and folded states, respectively. ► At its crossover temperature, a crowder changes from a destabilizer to a stabilizer.